Cultural adaptation and validation of the performance assessment of self-care skills among older people in community - Siti Noraini Asmuri; Masne Kadar; Nor Afifi Razaob; Chai, Siaw Chui; Hanif Farhan Mohd Rasdi; Nur Syahira Atiqah Arifin (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Performance Assessment of Self-care Skills (PASS-Home) is a client-centered, performance-based, criterion-reference, observational form designed to capture client’s performance skills in completing daily task activities. The aim of the study was to describe the process of translating, adapting and validating the PASS-Home from English language version into a Malay language version. The development of the translated Malay version of the PASS-Home consisted of two stages. Stage one involved the exclusion of the items that were not culturally relevant to the Malaysian culture. Stage two involved the translation process. The five steps of the cross-cultural adaptation process were followed: (1) initial forward version; (2) a summary of recommendations by the expert panels; (3) the back-translation; (4) modifications of the translated Malay version of PASS and a summary of problems found during the pre-testing, and (5) the final version of the PASS Malay Version (M-PASS). A total of five items from the PASS-Home were omitted in the Malay version (M-PASS) and another five items that were considered as suitable in Malaysian context were added in the M-PASS. The Content Validation Index (CVI) showed perfect agreement with an average of I-CVI was reported at 0.99 and S-CVI/universal agreement (S-CVI/UA) was at 0.93. Test-retest reliabilty showed that the M-PASS were highly reliable reported of its three main constructs of Independence (ICC=0.706), Safety (ICC=0.906) and Adequacy (ICC=0.950). M-PASS showed strong evidence as a valid and reliable assessment in evaluating the functional level of older people who live independently in community.